One-stage surgical management for advanced dilated cardiomyopathy combined with aortic sinus aneurysm: a case report - Xu, Wenliu; Wang, Chaojie; Zou, Zengxiao; Wang, Ge; Tan, Songtao; Fan, Xiaoping (Frontiers in Cardiovascular Medicine, 2025)
IntroductionLeft ventricular assist device (LVAD) implantation is a highly effective procedure for the management of selected advanced heart failure patients, prolonging patient life and improving quality. Additional cardiac pathologies, especially valvular regurgitation or coronary heart disease, are common in LVAD recipients, whereas reports on the surgical management of heart failure combined with aortic disease are rare.Case presentationWe present a case of a 60-year-old patient with an aortic sinus aneurysm, aortic regurgitation, and end-stage heart failure. LVAD implantation was performed concomitantly with the Bentall procedure and Cabrol shunt technique. The patient was discharged uneventfully on postoperative day 26. This suggests that combining LVAD implantation with additional cardiovascular procedures could be an alternative strategy for patients with complex heart failure conditions.ConclusionLVAD implantation combined with additional aortic surgery can be a feasible alternative with acceptable risk, especially for patients who have elected to pursue LVAD as destination therapy. Successful outcomes require adequate preoperative evaluation, experienced cardiac surgeons, and close postoperative care.